INFLUENCE OF CAPITAL STRUCTURE AND PROFITABILITY ON COMPANY VALUE - Heru Harmadi Sudibyo (Jurnal Scientia, 2023)
This study aims to analyze the impact of capital structure and profitability on firm value in the food and beverage sub-sector of manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2022. The sample consists of 10 companies selected through purposive sampling. Data is collected through written votes, and secondary data is obtained from www.idx.co.id. The analytical methods used include regression and correlation tests, conducted using SPSS version 25.0. The findings indicate that capital structure (DER) does not influence firm value, while profitability (ROE) has a strong positive effect on the company's value. Simultaneously, both capital structure (DER) and profitability (ROE) significantly affect firm value, as evidenced by an f-count of 1.418, surpassing the f-table value of 3.20.